Thermal requirements for the embryonic development of Periplaneta americana (L.) (Dictyoptera: Blattidae) with potential application in mass-rearing of egg parasitoids - Bressan-Nascimento, S.; Oliveira, D. M. P.; Fox, E. G. P. [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
The embryonic development of oothecae of Periplaneta americana was evaluated under four different constant temperatures (5, 10, 15, 20, 25, 30, and 35 degrees C and also at different exposure times at <5 degrees C. Their suitability as hosts after the treatment for the parasitoids Evania appendigaster and Aprostocetus hagenowii was also assessed. Temperatures of 5, 10, 15, and 35 degrees C adversely affected the development of the cockroaches, and exposure times to <5 degrees C longer than 5 days sufficed to kill all the embryos in the oothecae. The lower thermal threshold for complete development of P. americana was estimated to be 6.8 degrees C, with a required total amount of 900.9 degree-days. Cold-killed oothecae were still fit for the development of parasitoids. Parasitism rates of A hagenowii were higher than those of E appendigaster, although with lower emergence rates. Our results can be useful in aiding mass-rearing of these parasitoids for biological control programmes of A americana, and may help forecast the time of emergence of nymphs of American cockroaches in infested areas. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Mass rearing; Periplaneta americana; Evania appendigaster; Aprostocetus hagenowii; Cooling; Biological control